PEMETAAN SIMPANAN KARBON TANAMAN PENEDUH JALAN WOLTER MONGINSIDI KOTA MANADO - Vederica Agumanis; Johny S. Tasirin; Wawan Nurmawan (Universitas Sam Ratulangi, 2022)
AbstractThe aim of this research was to determine the variation in carbon storage of eachspecies, total carbon accumulation, and the contribution of carbon of each species to thetotal carbon accumulation in the Wolter Monginsidi street. Data collection was carriedout in December 2020, using the non-destructive method and analyzed using specificand general allometric formulas. The data was collected by means of a census of treeswith a diameter of â‰¥ 10 cm, which were found along Wolter Monginsidi street, startingfrom the Boboca Malalayang Monument to the Bahu Police Station. The results showedthat, Samanea saman had the highest carbon storage value of 50,10 tons/tree, followedby Ceiba pentandra and Garuga floribunda with carbon storage values of 4,09 tons/treeand 2,58 tons/tree. The accumulated total carbon storage of Wolter Monginsidi street is9.787,09 tons, with variations in the three street segments. The highest accumulation(2.222,72 tons/ha) was in the early segment. The average carbon storage each tree is14,18 tons/tree. Samanea saman contributed 71,4 %, Ceiba pentandra 5,8 % andGaruga floribunda 3,7 %, to the total carbon storage accumulation of WolterMonginsidi street.Keywords: Carbon, biomass, non-destructive, shade trees.